Bologna Process Stocktaking Report 2009 - Margarita García Sanchis (Servei de Formació Permanent i Innovació Educativa, Universitat de València, 2009)
This is a revision of the Bologna Process Stocktaking Report 2009, document appointed to the Ministerial Conference in Leuven / Lovain-la-Neuve (28-29 April 2009). This report reflects the analysis of the progress that has been made towards achieving the goals that were set by the Ministers at the London Conference (2007), and shows the state of the art of the Bologna Process and the development of the EAHE.